RELATIONSHIP BETWEEN VITAMIN D SERUM [25(OH)D] AND MORBUS HANSEN: A SYSTEMATIC REVIEW - Oktaviani Eka Puspasari (Berajah Journal, 2026)
Morbus Hansen (MH) is a chronic granulomatous infection caused by Mycobacterium leprae, characterized by anesthesia, peripheral nerve thickening, and the presence of acid-fast bacilli (AFB) on bacteriological examination. Vitamin D is known to play an important immunomodulatory role in the immune response to mycobacterial infections. This study aims to review existing research on the relationship between serum levels of 25-hydroxyvitamin D [25(OH)D] and Morbus Hansen. A critical analysis was performed on scientific articles retrieved from PubMed, Google Scholar, and ScienceDirect databases, covering publications from the past 10 years that discussed vitamin D levels in patients with Morbus Hansen. Five articles meeting the inclusion criteria for this study. Serum vitamin D levels in Morbus Hansen patients were lower compared to healthy controls and showed a significant association with the clinical type of MH. Patients with the paucibacillary type had higher vitamin D levels than those with the multibacillary type. Vitamin D plays a role in the immune response against Mycobacterium leprae, and vitamin D deficiency may increase the risk and severity of the disease